Divulgação científica no Amazonas: uma análise das matérias de capa de revista Amazonas faz ciência - Neves, Aline Cristina Oliveira das (2013)
This study aimed to analyze the cover material of Amazonas faz Ciência magazine, which is printed by Foundation for Research Support of the State of Amazonas. The corpus consisted of cover stories over 22 issues of the magazine, covering the years 2005 to 2011. The research is based on qualitative as well as quantitative data for a better illustration. We tried to observe the different resources used in the texts to disseminate science, enlightened by the notion of shown heterogeneity, defined by Authier-Revuz (1998), which covers aspects linguistically describable as reported speech, quotes, and parentheses. The results showed that the magazine plays an important role in the dissemination of science and the actions of Science, Technology and Innovation state public system. It has also been demonstrated that the topics which focused on local research and programs offered in this area stimulate debate in the state; that the reported direct speech had a higher incidence in the texts analyzed and the voice of authority is a resource widely used by journalists/science communicators